(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Asyndetic compound sentences are comprehensively investigated in the article, it is emphasized the specifics of their formal-grammatical and semantic-syntactic organization. The characteristic features that make the admission of certain asyndetic structures to compound sentences are determined; it was stated that the most important of these signs is a grammatical equality of predicate parts as well as non-directional syntactic connection between them.